Reversal of rivaroxaban-induced anticoagulation with prothrombin complex concentrate, activated prothrombin complex concentrate and recombinant activated factor VII in vitro - Perzborn, Elisabeth; Heitmeier, Stefan; Laux, Volker; Buchmüller, Anja (Thrombosis research, 2014)
Anticoagulation therapies carry a risk of bleeding; reversal agents may be beneficial in cases of severe bleeding even for anticoagulants with a relatively short half-life, such as the oral factor Xa inhibitor rivaroxaban. We investigated the in vitro reversal effect of prothrombin complex concentrate (PCC; 0.2-1.0U/mL), activated PCC (aPCC; 0.2–1.0U/mL) and recombinant activated factor VII (rFVIIa; 5–50μg/mL) on rivaroxaban-induced (200–1000ng/mL) changes in prothrombin time (PT) and thrombin generation (TG) in plasma, and in thromboelastometry (clotting time [CT]) in whole blood from healthy subjects. All three agents were partially effective in reversing rivaroxaban-induced anticoagulation but showed different profiles. rFVIIa and aPCC were more effective than PCC in reversing prolongations of PT, CT and TG lag time; rFVIIa was more effective than aPCC. However, the reversal effect reached a plateau with a maximal effect of approximately 50%. Inhibition of maximum thrombin concentration was slightly reversed by these agents; aPCC was the most effective. In contrast, inhibition of endogenous thrombin potential (ETP) was strongly reversed by aPCC, with significant increases over baseline at low rivaroxaban concentrations. Compared with aPCC, PCC showed a similar but less effective reversal profile. rFVIIa reversed ETP inhibition by approximately 50%. The extent of reversal by aPCC, PCC and rFVIIa was dependent on the parameter measured in rivaroxaban-anticoagulated plasma or blood. ETP measurements may have predictive power for assessing the reversal potential of PCC or aPCC and may be used to indicate an increased prothrombotic risk.